Effects of a ferment soy product on the adipocyte area reduction and dyslipidemia control in hypercholesterolemic adult male rats - Cheik, Nadia Carla; Rossi, Elizeu Antonio [UNESP]; Fernandes Guerra, Ricardo Luis; Tenorio, Neuli Maria; Oller do Nascimento, Claudia Maria; Viana, Fabiana Pavan; Jovenasso Manzoni, Marla Simone; Carlos, Iracilda Zeppone [UNESP]; da Silva, Patricia Leao; Vendramini, Regina Célia [UNESP]; Damaso, Ana Raimunda (Biomed Central Ltd., 2008)
Background: Available data on the effects of a fermented soy product enriched with Enterococcus faecium and Lactobacillus Jugurti on circulating lipids and adiposity are not completely settled. This study aimed to observe the effects of a fermented soy product enriched with Enterococcus faecium and Lactobacillus Jugurti on central obesity and dyslipidemia control in Wistar adult male rats.Methods: Over a period of 8 weeks, animals had ad libitum food intake and water consumption as well as body weight and food consumption was monitored. The animals were assigned to four different experimental groups: Control Group (C); Control + Fermented Product Group (CPF); Hypercholesterolemic diet group (H); and Hypercholesterolemic + Fermented Product Group (HPF). The HPF and CPF groups received an intragastric administration of 1 ml of fermented product daily. After the experimental period the animals were killed by decapitation, blood was collected to measure cholesterol, triglycerides and HDL-cholesterol plasma concentration. Adipocyte circumference, lipolysis and lipogenis rates were measures using epididymal and retroperitoneal white adipose tissues.Results: The results demonstrated that 1 ml/day/rat of the fermented soy product promoted important benefits such as reduced cholesterolemia in hypercholesterolemic diet group and the adipocyte circumference in both control and hypercholesterolemic diet group.Conclusion: The fermented soy product enriched with Enterococcus faecium and Lactobacillus Jugurti decreased circulating lipids levels and reduced adipocyte area in rats.